Chronic exposure to volcanic gaseous elemental mercury : using wild Mus musculus to unveil its uptake and fate - Camarinho, Ricardo (2021)
Volcanoes are a natural source of gaseous elemental mercury (GEM) (Hg0). Monitoring GEM releases of volcanic origin has been widely studied; however, few studies have been performed about the biomonitoring of species exposed to GEM, rendering an unknown risk to the worldwide populations living in the vicinity of an active volcano. In this pilot study, we used Mus musculus as a bioindicator species to understand to what extent lungs are the main route of mercury uptake in populations chronically exposed to active volcanic environments. Autometallographic silver protocol was used to detect mercury deposits in the histological lung slides. Abundant mercury deposits were found in the lungs of specimens captured at the site with volcanic activity (Furnas Village, S. Miguel Island—Azores). The presence of mercury in the lungs could represent not only hazardous effects to the lung itself but also to other tissues and organs, such as brain and kidneys. This study confirms that the main uptake route for GEM is the lungs and that, even at very low concentrations in the environment, a chronic exposure to Hg0 results in its bioaccumulation in the lung tissue. These results reinforce that biomonitoring studies should be combined with monitoring classical approaches in order to better characterize the risks of exposure to Hg0 in volcanic environments.